Meningkatkan Kemampuan Berpikiri Kritis dan Kreatifitas Siswa dengan Model Problem Base Learning (PBL) pada Siswa Kelas IV Fase B di SD Negeri 12 Sungai Risap - Paskarada Gerada; Dicky Aprianto; Hedwigis Dian Permatasari (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to describe the application of the Problem Base Learning (PBL) model in improving the critical and creative thinking abilities of class IV phase B students at SD 12 Sungai Risap. As well as describing how the critical thinking skills and creativity of class IV phase B students at SD 12 Sungai Risap increased after implementing PBL. The type of research is Classroom Action Research (PTK), entitled